LINGKUNGAN ALAM SEBAGAI MEDIA PEMBELAJARAN UNTUK MENGENALKAN KEKUASAAN ALLAH PADA ANAK USIA SEKOLAH DASAR DI PONDOK PESANTREN AL MAWADDAH KUDUS - Rochanah Rochanah (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2018)
Abstract Learning activities are not always in classroom, but can also occur outside the classroom. Empowering the environment as a learning medium is interesting and fun for students, not only learning directly to nature but students are taught how to know the power of Allah SWT, because this is the cultivation of religious values is very important for elementary school children. The method used in this study is descriptive-analytical research. Data collection techniques through observation, interviews and documentation. The results showed that; the concept offered by Al Mawaddah Islamic boarding school to introduce the power of God includes; dragon fruit cultivation, living pharmacy, hydroponics, rabbit garden, garra rafa fish therapy.